2017
DOI: 10.1038/ncb3500
|View full text |Cite
|
Sign up to set email alerts
|

CUL-2LRR-1 and UBXN-3 drive replisome disassembly during DNA replication termination and mitosis

Abstract: Replisome disassembly is the final step of DNA replication in eukaryotes, involving the ubiquitylation and CDC48-dependent dissolution of the CMG helicase (Cdc45-MCM-GINS). Using Caenorhabditis elegans early embryos and Xenopus egg extracts, we show that the E3 ligase CUL-2LRR-1 associates with the replisome and drives ubiquitylation and disassembly of CMG, together with the CDC-48 co-factors UFD-1 and NPL-4. Removal of CMG from chromatin in frog egg extracts requires CUL2 neddylation, and our data identify ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
246
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(271 citation statements)
references
References 55 publications
24
246
1
Order By: Relevance
“…Previous work showed that depletion of the orthologues of Ufd1 or Npl4 led to persistence of Cdc45 or GINS on mitotic chromatin in early embryos of the nematode Caenorhabditis elegans or in egg extracts of the frog Xenopus laevis (Franz et al., 2011). Although these findings were thought to reflect a post-replicative role for UFD1-NPL4-CDC48 in extracting GINS and Cdc45 (but not Mcm2–7) from chromatin during mitosis, we found that depletion of UFD-1, NPL-4, or CDC-48 in C. elegans early embryos leads to persistence of ubiquitylated CMG helicase (Sonneville et al., 2017). Moreover, UFD1-NPL4-p97 are recruited to chromatin during DNA replication termination in frog egg extracts (Dewar et al., 2017) and associate with ubiquitylated CMG helicase (Sonneville et al., 2017).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Previous work showed that depletion of the orthologues of Ufd1 or Npl4 led to persistence of Cdc45 or GINS on mitotic chromatin in early embryos of the nematode Caenorhabditis elegans or in egg extracts of the frog Xenopus laevis (Franz et al., 2011). Although these findings were thought to reflect a post-replicative role for UFD1-NPL4-CDC48 in extracting GINS and Cdc45 (but not Mcm2–7) from chromatin during mitosis, we found that depletion of UFD-1, NPL-4, or CDC-48 in C. elegans early embryos leads to persistence of ubiquitylated CMG helicase (Sonneville et al., 2017). Moreover, UFD1-NPL4-p97 are recruited to chromatin during DNA replication termination in frog egg extracts (Dewar et al., 2017) and associate with ubiquitylated CMG helicase (Sonneville et al., 2017).…”
Section: Discussionmentioning
confidence: 59%
“…Although these findings were thought to reflect a post-replicative role for UFD1-NPL4-CDC48 in extracting GINS and Cdc45 (but not Mcm2–7) from chromatin during mitosis, we found that depletion of UFD-1, NPL-4, or CDC-48 in C. elegans early embryos leads to persistence of ubiquitylated CMG helicase (Sonneville et al., 2017). Moreover, UFD1-NPL4-p97 are recruited to chromatin during DNA replication termination in frog egg extracts (Dewar et al., 2017) and associate with ubiquitylated CMG helicase (Sonneville et al., 2017). These data indicate a conserved mechanism for CMG disassembly from yeast to animals.…”
Section: Discussionmentioning
confidence: 59%
“…The role of SMC5/6 in facilitating DNA repair may be manifested via recruitment and/or Sumoylation of BLM, already reported to act jointly with FANCD2 and SMC5/6/NSMCE2 in certain conditions of replication stress [21,64]. This latter envisaged function may involve the ubiquitin and SUMO ligase activity of the SMC5/6 complex and potentially facilitate replisome disassembly during replication termination [65] or cohesin removal to facilitate repair completion and normal chromosome structure in prophase [66]. This latter envisaged function may involve the ubiquitin and SUMO ligase activity of the SMC5/6 complex and potentially facilitate replisome disassembly during replication termination [65] or cohesin removal to facilitate repair completion and normal chromosome structure in prophase [66].…”
Section: Discussionmentioning
confidence: 93%
“…MCM is then unloaded from the chromatin following DNA synthesis in a ubiquitin-dependent manner (Dewar, Budzowska et al, 2015, Dewar, Low et al, 2017, Moreno, Bailey et al, 2014, Sonneville, Moreno et al, 2017. In initial experiments, we determined the effect of STN1 knockdown on the levels of chromatin-bound MCM in EdU positive versus negative cells ( Figure 1B and 2A).…”
Section: Stn1 Depletion Leads To Increased MCM In G1 and S-phasementioning
confidence: 99%